2016
DOI: 10.3389/fnhum.2016.00592
|View full text |Cite
|
Sign up to set email alerts
|

Neural Differences between Covert and Overt Attention Studied using EEG with Simultaneous Remote Eye Tracking

Abstract: Research on neural mechanisms of attention has generally instructed subjects to direct attention covertly while maintaining a fixed gaze. This study combined simultaneous eye tracking and electroencephalogram (EEG) to measure neural attention responses during exogenous cueing in overt attention shifts (with saccadic eye movements to a target) and compared these with covert attention shifts (responding manually while maintaining central fixation). EEG analysis of the period preceding the saccade latency showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(106 citation statements)
references
References 65 publications
(125 reference statements)
10
92
1
3
Order By: Relevance
“…Saccade latencies were significantly longer in the competition condition than in the non‐competition condition, and latencies under competition significantly decreased with age, ‘Sticky’ fixations were more frequent under competition than non‐competition and more frequent in very young infants. These findings are in line with previous research demonstrating longer saccade latencies when disengagement from a central stimulus is required, using the FSP and the gap paradigm (Atkinson & Braddick, ; Atkinson et al, , ; Harris & MacFarlane, ; Hood & Atkinson, ; Johnson et al, ; Kulke et al, ; Kulke, Atkinson, & Braddick, ). The additional analysis including the full infant data set demonstrated that the behavioural findings show a robust effect and that the strict EEG exclusion criteria did not bias the sample in regards to behavioural findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Saccade latencies were significantly longer in the competition condition than in the non‐competition condition, and latencies under competition significantly decreased with age, ‘Sticky’ fixations were more frequent under competition than non‐competition and more frequent in very young infants. These findings are in line with previous research demonstrating longer saccade latencies when disengagement from a central stimulus is required, using the FSP and the gap paradigm (Atkinson & Braddick, ; Atkinson et al, , ; Harris & MacFarlane, ; Hood & Atkinson, ; Johnson et al, ; Kulke et al, ; Kulke, Atkinson, & Braddick, ). The additional analysis including the full infant data set demonstrated that the behavioural findings show a robust effect and that the strict EEG exclusion criteria did not bias the sample in regards to behavioural findings.…”
Section: Discussionsupporting
confidence: 91%
“…Wave plots of occipital responses. Occipital areas show an overall negative response in both hemispheres with more distinct and earlier peaks in infants aged 5.5-7.5 months (bottom) than for ages 1.5-2.5 months (top) disengagement from a central stimulus is required, using the FSP and the gap paradigm (Atkinson & Braddick, 1985;Atkinson et al, 1988Atkinson et al, , 1992Harris & MacFarlane, 1974;Hood & Atkinson, 1993;Johnson et al, 1991;Kulke et al, 2015;Kulke, Atkinson, & Braddick, 2016).…”
Section: Occipital Responsementioning
confidence: 99%
“…Para reações de apertar as teclas em que os olhos estavam fixados sobre o centro os eventos foram caracterizados como desempenhos por atenção encoberta e para reações com os olhos sobre o asterisco ou em uma das caixas a atenção foi caracterizada como desempenho por direcionamento ocular [5][6] [9]. O software utilizado para registrar as coordenadas oculares foi o IView X [11].…”
Section: Materiais E Métodosunclassified
“…Estas latências menores foram interpretadas como evidência da orientação da atenção visual aos locais de importância no campo visual. E com isso, entende-se que o que é avaliado é o desempenho por atenção encoberta, pois todos os estímulos são apresentados dentro do mesmo campo visual, mas se responde mais eficientemente a estímulos em locais específicos [5]. Os participantes são orientados a manter o olhar fixo no centro da dela do computador: a atenção é considerada encoberta por não envolver orientação verificável dos olhos [6].…”
Section: Introductionunclassified
“…Alternatively, stimulus onset related eyemovement artefacts can be avoided by extracting only short intervals (180 ms), so that most eyemovements occur after the extracted time window (Kulke, 2019;Kulke et al, 2015Kulke et al, , 2016aKulke et al, , 2016bKulke, Atkinson, & Braddick, 2020). However, guides to EEG methods recommend digital filters to be applied to the EEG data before these time windows are extracted to avoid edge artefacts (e.g.…”
mentioning
confidence: 99%